THE ANALYZE OF INCOME STRUCTURE AND CONSUMPTION PATTERNS OF PADDY FARMER HOUSEHOLDS IN BUNGA RAYA SUB-DISTRICT SIAK DISTRICT - Fikri Munawar; Jum'atri Yusri; Novia Dewi (Fakultas Pertanian, Universitas Riau, 2017)
This study was aimed at: 1) identifying household expenditure structures of paddy farmers in Bunga Raya Sub district Siak District; 2) analyzing household consumption patterns of paddy farmers in Bunga Raya Sub district Siak District and 3) analyzing dominant factors affecting consumption patterns of paddy farmers in Bunga Raya Sub district Siak District. The research was conducted at two villages in Bunga Raya Sub district, which were Bunga Raya and Kemuning Muda by using survey method. Random sampling was used for selecting samples by interviewing 42 respondents. Binary logistic model of expenditure structures and consumption patterns were used to analyze the data. According to the analysis of income structure, the largest household income was based on paddy farming. Consumption patterns of paddy farmers household showed that food expenditure was as much as non-food expenditure. The dominant factors affecting food consumption patterns of paddy farmers household were income and number of household members. Relationship between status of occupation and expenditure allocation opportunity was inversely proportional. This means that the smaller the household income and the greater the number of family members, the higher the opportunity for farmers to allocate their expenditure on food consumption.